Education and Alcohol Consumption among Older Americans; Black–White Differences - Assari, Shervin; Lankarani, Maryam Moghani (Frontiers in Public Health, 2016)
Purpose Although the link between education and alcohol consumption is known, limited information exists on racial differences in this link. We conducted the current study to test Black–White differences in the association between education and alcohol consumption among older adults in the U.S. Methods This cross-sectional survey enrolled 1,493 Black (n = 734) and White (n = 759) older adults (age 66 or more) in U.S. Data came from the Religion, Aging, and Health Survey, 2001. Race, demographics, socioeconomics, and alcohol consumption were measured. Independent variable was education level. Outcome was alcohol consumption. Race was the focal moderator. Logistic regression was used for data analysis. Results Education was positively associated with ever drinking in the pooled sample. However, race interacted with education level on drinking, suggesting a smaller effect of education on drinking for Blacks compared to Whites. Among Whites, high-school graduation and college graduation were associated with increased odds of ever drinking, net of covariates. Among Blacks, high-school graduation, but not college graduation, was associated with ever drinking. Conclusion Blacks and Whites differ in how socioeconomic status (i.e., education) shapes behaviors, especially health behaviors (i.e., drinking). How race modifies consequences and correlates of social determinants of health is not yet clear. College graduation may result in the same level of change to the social network and income of race group members. Weaker effect of education on health of Blacks may be due to the structural role of race and racism that has resulted in lower job availability and pay for Blacks.